Forest type diversity on carbon stocks: Cases of recent land cover conditions of tropical lowland, swamp, and peatland forests in West Kalimantan, Indonesia - DWI ASTIANI; MUJIMAN MUJIMAN; ANDJAR RAFIASTANTO (Society for Indonesian Biodiversity, 2017)
Abstract. Astiani D, Mujiman, Rafiastanto A. 2017. Forest type diversity on carbon stocks: Cases of recent land cover conditions of tropical lowland, swamp, and peatland forests in West Kalimantan, Indonesia. Biodiversitas 18: 137-144.Tropical forests constitute for a large concentrated carbon pools, ultimately in tropical peatland forest since this forest type sink carbon both in the vegetation and its underlying peat. However, these forests recently experienced a lot of pressures from anthropogenic disturbances. A study was conducted to estimate carbon stocks of degraded tropical lowland, swamp, and peatland forests in Kayong Utara West Kalimantan. Above ground survey was conducted using stratified sampling based on the differences in spectra of Landsat 7 ETM+ according to the land cover gradation or vegetation formations. The study area was classified based on the canopy closures and forest/landcover types and grouped into low and high degraded lowland forest, low and high degraded peat forest, low and high degraded swamp forest, shrub land, and mixed agricultural land. Aboveground carbon stocks in each group was estimated by purposively assessing all carbon sources within 5-11 plots of 20 m x 100 m area. Belowground carbon was also measured on peatland. Results show that among the groups, the highest to the lowest order of aboveground carbon sink consecutively were low degraded swamp, low degraded lowland, low degraded peatland, high degraded swamp, high degraded peatland, high degraded lowland forests, mixed agricultural land, and shrub land (269.1 to 46.3 ton C/ha) plus other biomass sources recruited from belowground roots. It is demonstrated that forest degradation and land cover changes reduce amount of above ground carbon stocks and thus could result large amount of carbon loss from forests. Surprisingly, our results demonstrated that 0.5-5.2 m belowground carbon in peatland contribute to large amount of carbon Each meter depth of those fibrist to hemist peat sinked 634 ton C/ha. It is estimated that the 22,600 ha area of overall forest types/ land covers sink 2.5 million of aboveground and 5,570 ha peatland area hold 9.2 million of below ground carbon. This amount of carbon is potential sink of carbon yet could be a huge losses if peatland forest and land cover changes continued. Keywords: Aboveground carbon, belowground carbon stocks, degraded forest, land cover change, forest typesÂ